A membrane-less electrolyzer with porous walls for high throughput and pure hydrogen production. Issue 9 (31st March 2021) - Hadikhani, Pooria; Hashemi, S. Mohammad H.; Schenk, Steven A.; Psaltis, Demetri
Abstract : The porous wall electrolyzer utilizes two porous walls between nucleation sites in order to achieve high hydrogen production rates with high purity. Abstract : Membrane-less electrolyzers utilize fluidic forces instead of solid barriers for the separation of electrolysis gas products. These electrolyzers have low ionic resistance, a simple design, and the ability to work with electrolytes at different pH values. However, the interelectrode distance and the flow velocity should be large at high production rates to prevent gas cross over. This is not energetically favorable as the ionic resistance is higher at larger interelectrode distances and the required pumping power increases with the flow velocity. In this work, a new solution is introduced to increase the throughput of electrolyzers without the need for increasing these two parameters. The new microfluidic reactor has three channels separated by porous walls. The electrolyte enters the middle channel and flows into the outer channels through the wall pores. Gas products are being produced in the outer channels. Hydrogen cross over is 0.14% in this electrolyzer at flow rate = 80 mL h −1 and current density ( j ) = 300 mA cm −2 . This cross over is 58 times lower than hydrogen cross over in an equivalent membrane-less electrolyzer with parallel electrodes under the same working conditions. Moreover, the addition of a surfactant to the electrolyte further reduces the hydrogen cross over by 21% and the overpotential by 1.9%. This is due to the positive effects of surfactants on the detachment and coalescence dynamics of bubbles. The addition of the passive additive and implementation of the porous walls result in twice the hydrogen production rate in the new reactor compared to parallel electrode electrolyzers with similar hydrogen cross over.